2009
DOI: 10.1038/cdd.2009.184
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis, necrosis and secondary necrosis converge on similar cellular disintegration features

Abstract: Necroptosis, necrosis and secondary necrosis following apoptosis represent different modes of cell death that eventually result in similar cellular morphology including rounding of the cell, cytoplasmic swelling, rupture of the plasma membrane and spilling of the intracellular content. Subcellular events during tumor necrosis factor (TNF)-induced necroptosis, H2O2-induced necrosis and anti-Fas-induced secondary necrosis were studied using high-resolution time-lapse microscopy. The cellular disintegration phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
290
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(320 citation statements)
references
References 43 publications
(62 reference statements)
15
290
1
2
Order By: Relevance
“…It is possible that the cell death inhibitory effect of zVAD-fmk when used at increasing concentrations observed here reflects the progressive inhibition of caspases and other cysteine proteases such as calpains and cathepsins that are also targets of zVADfmk (45). In agreement with a role for cathepsins in the cell death mechanism, lysosomal membrane permeabilization was recently described as a common denominator in several necrotic death modes including necroptosis (46).…”
Section: Discussionsupporting
confidence: 59%
“…It is possible that the cell death inhibitory effect of zVAD-fmk when used at increasing concentrations observed here reflects the progressive inhibition of caspases and other cysteine proteases such as calpains and cathepsins that are also targets of zVADfmk (45). In agreement with a role for cathepsins in the cell death mechanism, lysosomal membrane permeabilization was recently described as a common denominator in several necrotic death modes including necroptosis (46).…”
Section: Discussionsupporting
confidence: 59%
“…Towards this, we challenged primary macrophages with pyroptosis inducers and lysosomedestabilizing agents in the presence of lysosomotropic agents. We found that the lysosomotropic agent NH 4 Cl blocked necrotic cell death mediated by LLOMe and the pyroptosis inducer LT, yet with distinct efficiencies (Fig. 1C).…”
Section: Resultsmentioning
confidence: 86%
“…1C). Significantly lower NH 4 Cl concentrations were required to block LT-induced cell death compared to LLOMe-induced cell death (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike apoptosis, necrosis is described as an uncontrolled and accidental form of cell death until genetically determined, regulated processes that mediates necrotic cellular demise, which were recently identified and are now termed programmed necrosis or necroptosis 14, 15. Necroptosis shares with necrosis the fact that dying cells display the morphological features of necrosis but not of apoptosis, but is highly regulated by an intracellular protein platform 14, 16. Recent advances have shown that activation of the kinase domain of receptor‐interacting protein1 (RIP1) and the assembly of RIP1/3‐containing signalling complex (termed the necrosome) mediated necroptosis contributes to the pathogenesis in preclinical models of brain 17, 18, heart 19, 20, and kidney 21, 22 I/R injury, which can be protected by using the RIP1 kinase inhibitor necrostatin (Nec)‐1.…”
Section: Introductionmentioning
confidence: 99%